Ecophysiology of Antarctic Vascular Plants: An Update on the Extreme Environment Resistance Mechanisms and Their Importance in Facing Climate Change - Constanza F. Ramírez; Lohengrin A. Cavieres; Carolina Sanhueza; Valentina Vallejos; Olman Gómez-Espinoza; León A. Bravo; Patricia L. Sáez (Plants, 2024)
Antarctic flowering plants have become enigmatic because of their unique capability to colonize Antarctica. It has been shown that there is not a single trait that makes Colobanthus quitensis and Deschampsia antarctica so special, but rather a set of morphophysiological traits that coordinately confer resistance to one of the harshest environments on the Earth. However, both their capacity to inhabit Antarctica and their uniqueness remain not fully explained from a biological point of view. These aspects have become more relevant due to the climatic changes already impacting Antarctica. This review aims to compile and update the recent advances in the ecophysiology of Antarctic vascular plants, deepen understanding of the mechanisms behind their notable resistance to abiotic stresses, and contribute to understanding their potential responses to environmental changes. The uniqueness of Antarctic plants has prompted research that emphasizes the role of leaf anatomical traits and cell wall properties in controlling water loss and CO2 exchange, the role of Rubisco kinetics traits in facilitating efficient carbon assimilation, and the relevance of metabolomic pathways in elucidating key processes such as gas exchange, nutrient uptake, and photoprotection. Climate change is anticipated to have significant and contrasting effects on the morphophysiological processes of Antarctic species. However, more studies in different locations outside Antarctica and using the latitudinal gradient as a natural laboratory to predict the effects of climate change are needed. Finally, we raise several questions that should be addressed, both to unravel the uniqueness of Antarctic vascular species and to understand their potential responses to climate change.